AOSRV: Development and preliminary performance assessment of a new robotic system for autonomous percutaneous vertebroplasty. Issue 6 (31st August 2022) - Huang, Junshen; Xing, Tong; Cheng, Ziying; Lu, Shixin; Li, Ming; Liang, Yuwei; Huang, Jiajun; Liao, Zhuangyao; Su, Kaihui; Wen, Guoming; Liang, Changchun; Che, Zhen; et al.
Abstract: Background: Percutaneous vertebroplasty (PVP) is one of the most effective treatments for patients with vertebral fracture that need surgical treatment, and surgical robotics are promising tools to provide surgeons with improved precision, surgical efficiency and reduce radiation exposure. However, there are currently few robotics that are developed to help assist with PVP. Methods: A new spinal surgical robotic system 'AOSRV' for autonomous vertebral puncture and bone cement injection was designed and customised in this study. To investigate its practical abilities and the advantages, we performed single‐segment/double‐segment PVP simulation surgeries on pig spinal specimens manually and using AOSRV. Results: By contrast with the freehand group (FG) in single‐segment (SS)/double‐segment (DS) surgery, the robotic group (RG) was superior in the operation time (RGSS = 21.14 ± 4.11 min, FGSS = 33.17 ± 6.83 min; RGDS = 42.39 ± 7.31 min, FGDS = 62.86 ± 20.39 min), puncture adjustments (RGSS = 2.30 ± 1.77, FGSS = 14.86 ± 5.46; RGDS = 3.91 ± 1.76, FGDS = 20.00 ± 7.76), intraoperative fluoroscopies (RGSS = 4.10 ± 1.52, FGSS = 20.57 ± 5.44; RGDS = 7.82 ± 1.40, FGDS = 25.91 ± 7.23) and bone cement leakage rate (RGSS = 30%, FGSS = 71.4%; RGDS = 38.6%, FGDS = 83.3%). Conclusions: AOSRV was successfully developed and had a promising preliminary performance. An innovative attempt was made for the blank space of the autonomous vertebroplasty surgical robotics, and it may shed a light on more promising applications in the future.